A method for determining glucose in lithium battery copper foil electroplating solution

By using phenol-sulfuric acid method and response surface analysis in the lithium battery copper foil plating solution, the problems of large and complexity of the glucose measurement method in the prior art are solved, and high accuracy and simple glucose concentration monitoring are achieved, ensuring copper Stability of foil quality.

CN115561186BActive Publication Date: 2024-12-13HONGHE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211075248.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-29
Publication Date
2024-12-13
Estimated Expiration
2042-10-29

AI Technical Summary

Technical Problem

The existing glucose determination methods have problems such as large system error, complex pretreatment process, many uncontrollable factors, high cost and complex operation in lithium battery copper foil electroplating solution. It is difficult to accurately determine glucose concentration, affecting the quality of copper foil.

Method used

The phenol-sulfuric acid method was used to perform glucose color development measurement. By adjusting the pH value, extracting copper ions, measuring the metal ion content, and optimizing the addition amount of phenol and sulfuric acid and the color development time, combined with the response surface analysis, a simple and highly accurate glucose was established. Determination method.

Benefits of technology

It realizes the accuracy of glucose measurement and reduces systematic errors, simplifies the pre-treatment process, reduces uncontrollable factors, improves the measurement precision and repeatability, and is suitable for the glucose concentration monitoring of lithium-ion copper foil electroplating solution, ensuring the quality of copper foil stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115561186B_ABST
    Figure CN115561186B_ABST
Patent Text Reader

Abstract

The invention discloses a method for determining glucose in a lithium-battery copper foil electroplating solution, comprising the following steps: sample pretreatment, determination of copper, nickel, iron and zinc, determination of glucose, and establishing a method for determining the content of glucose in a lithium-battery copper foil electroplating solution by optimizing the effects of the amount of phenol added, the amount of sulfuric acid added, the color development temperature and the color development time on the glucose absorbance. The optimization result is: take 2.0 mL of lithium-battery copper foil electroplating solution, add 0.8 mL of phenol and 7.0 mL of sulfuric acid, color develop for 15 minutes in a water bath at 50°C, take out and place in a cold water bath for 45 minutes, cool to room temperature, and measure the absorbance at an absorption wavelength of 490 nm. Under the optimal conditions, the linear correlation between glucose concentration and absorbance is good (r=0.9995), the spike recovery rate is 100.12%, the RSD is 0.76%, the precision RSD is 0.01%, and the repeatability RSD is 0.04%. The method of the present invention can meet the requirements for determining the glucose content in lithium battery copper foil electroplating solution, the determination result is accurate, the systematic error is small, the pretreatment process is simple, and the uncontrollable factors are low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glucose content determination in electroplating solution, and in particular relates to a method for determining glucose in lithium battery copper foil electroplating solution. Background Art

[0002] The electroplating solution is a liquid that can increase the current density range of the metal cathode, improve the appearance of the coating, and improve the antioxidant properties of the solution. Chromic anhydride-glucose electroplating solution is recognized by many copper foil manufacturers because of its simple process, no need for electroplating and easy operation. Chromic anhydride-glucose electroplating solution is made of chromic anhydride, glucose and water as the main raw materials. Glucose has high hydrophilicity and contains rich hydroxyl groups. It can adsorb oxygen ions on the surface of copper foil and saturate the chemical affinity of the surface of copper foil, thereby achieving passivation of copper foil. Cr3+ and Cr6+ in the chromic anhydride aqueous solution can oxidize the copper on the surface of copper foil to form a compact copper salt with good coverage, thereby changing the physical form and chemical structure of copper foil. The glucose solution in the passivation solution has a certain passivation and anti-oxidation effect. The adsorption of oxygen ions on the surface of glucose is a prerequisite for the formation of an excellent passivation film. Glucose and chromic anhydride have a synergistic effect. First, the adsorption film is formed by glucose, followed by the phase film of chromium. In lithium-ion batteries, copper foil is the most ideal cathode current collector material, so people's requirements for copper foil quality and control of copper foil are becoming more and more stringent. The control of copper foil surface passivation process is a key link in the production process. Too high or too low concentrations of glucose and chromic anhydride will affect the quality of copper foil, so controlling the concentration of glucose in the passivation solution is the key to measuring the quality of copper foil.

[0003] The methods for determining glucose include: oxidation-reduction titration, iodine starch system decolorization photometry, mid-infrared attenuated total reflectance, HPLC, glucose oxidase, iodine titration, polarimetry, and colorimetry. Monosaccharides other than glucose will also interfere with the measurement results, and the system error is large. The preparation of standard titration solutions by glucose oxidase and iodine titration takes a long time, is complicated to operate, has low glucose oxidase activity, and has many uncontrollable factors. The concentration, wavelength, and temperature of glucose in the polarimetry have a great influence on the accuracy of the measurement results. The HPLC method has high accuracy, but is costly, complicated to operate, time-consuming, and has high requirements for experimental conditions and equipment. The colorimetry method only requires an ultraviolet spectrophotometer for measurement, and the instrument operation is simple and fast with high accuracy. Therefore, it is necessary to develop a method for determining glucose in lithium copper foil electroplating solution with accurate measurement results, small system error, simple pretreatment process, and low uncontrollable factors. Summary of the invention

[0004] The object of the present invention is to provide a method for determining glucose in lithium battery copper foil electroplating solution, which has accurate determination results, small system error, simple pretreatment process and low uncontrollable factors.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for determining glucose in lithium battery copper foil electroplating solution, comprising the following steps:

[0006] A. Sample pretreatment

[0007] (1) Adjust the pH value of the solution

[0008] Place 20 mL of the plating solution in a 50 mL beaker, use 0.1 mol / L sodium hydroxide solution and 0.1 mol / L sulfuric acid solution as regulators, monitor the pH value of the solution with a pH meter, and stir while adjusting to make the solution evenly mixed until the pH reaches 3.5;

[0009] (2) Extraction of copper ions from electroplating solution

[0010] The copper ions in the electroplating solution were extracted with a water phase: oil phase ratio of 1:2. 5 mL of the adjustment solution in step (1) was measured and placed in a separatory funnel. 10 mL of 30% ZJ988 extractant was added. The mixture was shaken for 5 min, allowed to stand for 10 min, and the water phase was taken for later use.

[0011] (3) Preparation of sample solution

[0012] Measure 0.5 mL of the extract in step (2) and put it into a 100 mL volumetric flask, dilute to the mark with deionized water, and mix well for later use;

[0013] B. Determination of copper, nickel, iron and zinc

[0014] Turn on the power of the mainframe and hollow cathode lamp detector of the atomic absorption spectrophotometer and preheat for 15 minutes. At the same time, set the element detection parameters, turn on the air acetylene, air compressor and vacuum box switches in turn, ignite after everything is ready, and follow the prompts to draw the standard solution calibration curve and measure the metal ion absorbance in the electroplating solution, and then calculate the metal ion content in the electroplating solution according to the linear regression equation of the standard solution. Parallel determination is performed 3 times;

[0015] C. Determination of glucose

[0016] The sample solution is developed by the phenol-sulfuric acid method, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 mL of glucose standard solution are measured and placed in 25 mL stoppered colorimetric tubes, respectively, and water is added to 2.0 mL, and 2.0 mL of the sample solution in step (3) is taken, and distilled water is used as a reference; 0.8 mL of 6% phenol solution is added and shaken, and 7 mL of concentrated sulfuric acid solution is immediately added, and the mixture is placed at room temperature for 5 minutes, and then the mixture is colorized in a hot water bath at a temperature of 50° C. for 15 minutes, and then the mixture is cooled to room temperature in a cold water bath for 45 minutes; the absorbance is measured in a UV-visible spectrophotometer at a wavelength of 490 nm, and a regression equation is drawn to calculate the glucose content in the sample;

[0017] D. Result calculation

[0018] The metal ion content is calculated according to formula (1):

[0019]

[0020] Where:

[0021] X——the content of the substance to be tested in mg / mL;

[0022] Cx——mass concentration of any metal ion in the sample, mg / mL;

[0023] D——sample dilution multiple;

[0024] m——sample transfer volume, mL;

[0025] The extraction rate is calculated according to formula (2):

[0026]

[0027] Where:

[0028] R——extraction rate, %;

[0029] C0, Ce——Concentration of the ion to be measured in the solution before and after extraction, mg / L;

[0030] Glucose content was calculated according to formula (3):

[0031]

[0032] Where:

[0033] m——sample transfer volume, mL; 1000——conversion factor;

[0034] CA——glucose mass concentration in the sample, μg / mL;

[0035] V——sample fixed volume, mL;

[0036] The spike recovery rate was calculated according to formula (4):

[0037]

[0038] Where:

[0039] P——spike recovery, %;

[0040] C1——concentration of sample before spike addition, mg / mL;

[0041] C2——concentration of sample after spike, mg / mL;

[0042] C3——Concentration of standard solution added, mg / mL.

[0043] The beneficial technical effects of the present invention are:

[0044] 1. The present invention adopts the phenol-sulfuric acid method to develop the color of glucose in the electroplating solution and then determines its absorbance, and calculates the glucose content through a regression equation. The instrument operation is simple and fast with high accuracy.

[0045] 2. By measuring the content of copper, zinc, iron and nickel ions in the electroplating solution, the influence of metal ions on the determination of glucose content can be explored to avoid the interference of residual metal ions on the determination of glucose content.

[0046] 3. By optimizing the amount of phenol and sulfuric acid added and the optimal color development time and temperature, single factor experiments and response surface methods were used to obtain the optimal method conditions for determining the glucose content in lithium battery copper foil plating solution.

[0047] 4. The present invention starts with the preparation method of copper foil electroplating solution and the copper foil passivation treatment process, analyzes the basic components of the electroplating solution and the substances that may be introduced after copper electroplating, and explores the best method for determining the glucose content in the electroplating solution. The establishment of this method is conducive to enterprises to better monitor the concentration of glucose in the electroplating solution during the copper foil electroplating process, and prevent the glucose concentration from being too high or too low to affect the quality of the copper foil, which has a good development prospect and practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is the absorbance-wavelength curve;

[0049] Figure 2 is the standard working curve of glucose;

[0050] Figure 3 is the effect of the amount of phenol added on the absorbance;

[0051] Figure 4 is the effect of sulfuric acid addition on absorbance;

[0052] Figure 5 The effect of color development time on absorbance

[0053] Figure 6 is the effect of color development temperature on absorbance; DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with examples, which include but are not intended to limit the scope of protection of the present invention.

[0055] The present invention is further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and do not limit the scope of use of the present invention. The methods not described in detail in the examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. In addition, any similar detection content or material can use the present invention.

[0056] 1. Instruments, Equipment and Reagents

[0057] Instrument name: UV-visible spectrophotometer, atomic absorption spectrophotometer, water bath, electronic balance, electric heating blast drying oven, pH meter;

[0058] Reagent name: Glucose C6H 12 O6, phenol C6H6O, sodium hydroxide NaOH, sulfuric acid H2SO4, ZJ988 extractant, kerosene, thiourea H2NCSNH2, copper single element standard solution, zinc single element standard solution, iron single element standard solution, nickel single element standard solution.

[0059] 2. Instrument testing conditions

[0060] 2.1 Atomic absorption spectrophotometer measurement conditions

[0061] The working conditions for determining copper, nickel, iron and zinc ions in the plating solution using an atomic absorption spectrophotometer are shown in Tables 2-1 and 2-2.

[0062] Table 2-1 Atomic absorption spectrophotometer working conditions

[0063]

[0064] Table 2-2 Hollow cathode lamp working conditions

[0065]

[0066] 2.2 UV spectrophotometer measurement conditions

[0067] The UV photometer measurement conditions used to determine the glucose content in the plating solution are shown in Table 2-3.

[0068] Table 2-5 UV spectrophotometer working conditions

[0069]

[0070] 3. A method for determining glucose in a lithium battery copper foil electroplating solution, comprising the following steps:

[0071] 3.1 Sample pretreatment

[0072] 3.1.1 Adjusting the pH value of the solution

[0073] Place 20 mL of the plating solution in a 50 mL beaker, use 0.1 mol / L sodium hydroxide solution and 0.1 mol / L sulfuric acid solution as regulators, monitor the pH value of the solution with a pH meter, and stir while adjusting to make the solution evenly mixed until the pH reaches 3.5;

[0074] 3.1.2 Extraction of copper ions from electroplating solution

[0075] The copper ions in the electroplating solution were extracted with a water phase: oil phase ratio of 1:2. 5 mL of the adjustment solution in step (1) was measured and placed in a separatory funnel. 10 mL of 30% ZJ988 extractant was added. The mixture was shaken for 5 min, allowed to stand for 10 min, and the water phase was taken for later use.

[0076] 3.1.3 Preparation of sample solution

[0077] Measure 0.5 mL of the extract in "3.1.2" into a 100 mL volumetric flask, add deionized water to dilute to the mark, mix well and set aside.

[0078] 3.2 Determination of copper, nickel, iron and zinc

[0079] 3.2.1 Determination of copper, nickel, iron and zinc

[0080] Accurately transfer 0.5mL of the original plating solution into four 100mL volumetric flasks respectively, add deionized water to dilute to the scale, then turn on the power of the atomic absorption spectrophotometer host and hollow cathode lamp detector to preheat for 15 minutes, and set the element detection parameters at the same time, turn on the air acetylene, air compressor and vacuum box switches in turn, ignite when everything is ready, and follow the prompts to draw the standard solution calibration curve and determine the absorbance of metal ions in the plating solution, and then calculate the metal ion content in the plating solution according to the linear regression equation of the standard solution, and perform parallel determination 3 times; the linear regression equation is shown in Table 3-1.

[0081] Table 3-1 Linear regression equation

[0082]

[0083] It can be seen from Table 3-1 that in the standard solution of 0-50 mg / L, the linear equations of Cu, Ni, and Fe have a good linear relationship with the absorbance, and in the standard solution of 0-1.0 mg / L, the linear equation of Zn has a good linear relationship with the absorbance.

[0084] 3.2.2 Determination results of copper, nickel, iron and zinc

[0085] The metal ion content is calculated according to formula (1):

[0086]

[0087] Where:

[0088] X——the content of the substance to be tested in mg / mL;

[0089] Cx——mass concentration of any metal ion in the sample, mg / mL;

[0090] D——sample dilution multiple;

[0091] m——sample transfer volume, mL;

[0092] Each ion was measured three times in parallel, and the metal ion content, average content and SD value were shown in Table 3-2.

[0093] Table 3-2 Test results

[0094]

[0095] It can be concluded from Table 3-2 that the average copper ion content in the original electroplating solution is 113 mg / L, and the RSD is 2.06%, while the nickel, iron and zinc ion contents are not detected, indicating that the copper ion content in the original electroplating solution is relatively high, and the nickel, iron and zinc ion contents are so low that they are not detected.

[0096] 3.2.3Cu 2+ Impact on the results of the method

[0097] From the results of Table 3-2, we can see that the electroplating solution contains some copper ions, and the remaining Cu 2+ It will react with concentrated H2SO4 to form copper sulfate, which may affect the absorbance when measuring the glucose content in the sample. According to the method under "3.1.2", the Cu in the plating solution 2+ Extraction was performed and Cu was determined by the method in item "3.2.2" 2+ The extraction rate was calculated according to formula (2). The extraction conditions and test results are shown in Table 3-3.

[0098] Extraction rate calculation:

[0099]

[0100] Where:

[0101] R——extraction rate, %;

[0102] C0, Ce——Concentration of the ion to be measured in the solution before and after extraction, mg / L;

[0103] Table 3-3 Extraction conditions and test results

[0104]

[0105] It can be seen from Table 3-3 that after using ZJ988 to extract copper ions in the electroplating solution, the extraction rate of copper ions is 96.91%, indicating that the extraction conditions have a good extraction effect on copper ions in the electroplating solution and a high extraction rate.

[0106] 3.3 Determination of glucose

[0107] The sample solution was developed using the phenol-sulfuric acid method. 0, 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6 mL of the glucose standard solution were measured and placed in 25 mL stoppered colorimetric tubes, respectively. Water was added to 2.0 mL. Another 2.0 mL of the sample solution was taken, and distilled water was used as a reference. 0.8 mL of 6% phenol solution was added and shaken well. 7 mL of concentrated sulfuric acid solution was immediately added, and the mixture was placed at room temperature for 5 min. Then, the mixture was developed in a hot water bath at 50°C for 15 min. Then, the mixture was placed in a cold water bath for 45 min and cooled to room temperature. The absorbance was measured using a UV-visible spectrophotometer at a wavelength of 490 nm, and a regression equation was drawn to calculate the glucose content in the sample.

[0108] 3.3.1 UV detection wavelength optimization

[0109] Accurately pipette 2.0 mL of the plating solution and 5 μg / mL glucose standard solution into 25 mL stoppered colorimetric tubes, develop the color according to the experimental method in "3.3", use distilled water as a blank, scan the UV-visible spectrum at 400-800 nm, and determine the maximum absorption wavelength. The results are shown in Figure 1 .

[0110] Depend on Figure 1 It can be seen that the maximum absorption wavelength of glucose in the standard solution and the plating solution is 490nm, so the optimal absorption wavelength is 490nm.

[0111] 3.3.2 UV glucose determination standard curve and linear range

[0112] Prepare glucose solution and develop color according to item "3.3", measure absorbance at an absorption wavelength of 490nm, and draw a standard working curve of glucose with glucose concentration as the horizontal axis and absorbance as the vertical axis, as shown in the figure: Figure 2 The fitting results are: y = 0.01336x + 0.0365, r = 0.9995. The results show that within the glucose concentration range of 5.0 to 30 μg / mL, the linear relationship between the concentration of the glucose standard solution and the absorbance is good.

[0113] 3.4 Optimization of conditions for determination of glucose by phenol-sulfuric acid method

[0114] 3.4.1 Effect of phenol addition on absorbance

[0115] The effect of different phenol addition amounts on absorbance is shown in the following table. Figure 3 As shown. A 6% phenol solution was added, and the amount added increased from 0.2 mL to 1.0 mL. When the amount of phenol added reached 0.8 mL, the absorbance reached a maximum of 0.237. When it reached 1.0 mL, the absorbance of the solution gradually decreased. Therefore, 0.8 mL was the optimal amount of phenol added.

[0116] 3.4.2 Effect of sulfuric acid addition on absorbance

[0117] The results of the effect of different amounts of sulfuric acid on absorbance are as follows Figure 4 As shown, when the amount of concentrated sulfuric acid added is 1.0-9.0mL, the absorbance of the solution first decreases and then increases to 7.0mL, which is the maximum value. When the amount added is 9.0mL, the absorbance of the solution begins to decrease. If too little sulfuric acid is added, it will lead to incomplete hydrolysis of glucose, resulting in a decrease in absorbance, while excessive addition will make the furfural derivative unable to remain stable, causing a decrease in absorbance during hydrolysis. Therefore, 7.0mL is selected as the optimal addition amount.

[0118] 3.4.3 Effect of color development time on absorbance

[0119] The results of the effect of different color development time on absorbance are shown in Figure 5 When the color development time was 10-30 min, the absorbance first increased and then decreased, and became stable after 25 min. When the color development time was 15 min, the absorbance was the highest. Therefore, the optimal color development time was determined to be 15 min.

[0120] 3.4.4 Effect of color development temperature on absorbance

[0121] Depend on Figure 6 It can be seen that at 30-50℃, the absorbance of the solution gradually increases, the absorbance of the solution shows an increasing trend at 30-50℃, the absorbance is maximum at 50℃, and at 50-100℃, the absorbance gradually decreases, so 50℃ is selected as the optimal color development temperature.

[0122] 3.5 Best optimization conditions

[0123] Through the response surface analysis results, it was found that the best prediction conditions for the color analysis of glucose in the electroplating solution using the phenol-sulfuric acid method were: 0.84 mL of phenol, 6.71 mL of sulfuric acid, and 15.50 min of color development time. The predicted glucose content in the sample was 3.1028 mg / mL. After considering the actual operation, the actual method parameters were adjusted to 0.80 mL of phenol, 7.00 mL of sulfuric acid, and 15.00 min of color development time.

[0124] 3.5.1 Verification of the best optimization conditions

[0125] The plating solution was prepared using the sample pretreatment method of "3.1". A color reaction was performed when 0.80 mL of phenol and 7.00 mL of sulfuric acid were added and the color development time was 15.00 min. The absorbance was measured at a wavelength of 490 nm using an ultraviolet spectrophotometer. The measurements were repeated three times to calculate the glucose content and RSD.

[0126] Glucose content was calculated according to formula (3):

[0127]

[0128] Where:

[0129] m——sample transfer volume, mL; 1000——conversion factor;

[0130] C A ——Glucose mass concentration in the sample, μg / mL;

[0131] V——sample fixed volume, mL;

[0132] The results show that under this condition, the average content of glucose in the electroplating solution is 3.0771 mg / mL, which is close to the predicted value of 3.1028 mg / mL, indicating that the method is feasible. The RSD of three tests is 0.02%, which is less than 1.5%, and the accuracy and precision are good.

[0133] 4. Methodological Examination Experimental Results

[0134] 4.1 Instrument precision test results

[0135] Accurately take out 2mL of the sample solution in "3.1.3" and put it into a 25mL stoppered colorimetric tube. Perform color development according to the experimental method in "3.3". Use distilled water as a reference. At an absorption wavelength of 490nm, use a UV-visible spectrophotometer to continuously measure the absorbance 6 times and calculate the RSD value. The absorbance of the plating solution was measured 6 times in a row, and the results are shown in Table 3-4. As shown in Table 3-4, after measuring the absorbance of glucose in the plating solution 6 times in a row, the average content of glucose in the plating solution is 3.15mg / mL, and the RSD is 0.01%, which is less than 1.5%, indicating that the method has good precision.

[0136] Table 3-4 Precision test results

[0137]

[0138] 4.2 Repeatability experimental results

[0139] Repeatability experiments were performed on 6 groups of plating solutions, with each group measured three times in parallel. The test results are shown in Table 3-5. As shown in Table 3-5, the average content of glucose in the plating solution is 3.13 mg / mL, and the RSD is 0.04%, which is less than 1.5%, indicating that the method has good repeatability.

[0140] Table 3-5 Repeatability test results

[0141]

[0142] 4.3 Results of spike recovery and method precision experiments

[0143] In the spike recovery experiment, a glucose standard solution with a concentration of 15 μg / mL was added to the electroplating solution. The sample was measured three times in parallel at an absorption wavelength of 490 nm. The results are shown in Table 3-6.

[0144] Table 3-6 Spiked recovery test results (n=3)

[0145]

[0146] The results in Table 3-6 show that the recovery rate of spiked glucose in the plating solution is 100.12%, and the RSD is 0.76%, which is lower than 1.5%, and the method has good precision.

[0147] The spike recovery rate was calculated according to formula (4):

[0148]

[0149] Where:

[0150] P——spike recovery, %;

[0151] C1——concentration of sample before spike addition, mg / mL;

[0152] C2——concentration of sample after spike, mg / mL;

[0153] C3——Concentration of standard solution added, mg / mL.

[0154] The present invention takes lithium copper foil electroplating solution as the research object, uses phenol-sulfuric acid method as the color development method, and establishes and optimizes the determination method of glucose content in the electroplating solution. Through a single factor experiment, the amount of phenol added, the amount of sulfuric acid added and the color development time are selected as independent variables according to the experimental results to conduct a 3-factor 3-level "Box-Behnken" design analysis experiment. The following conclusions can be drawn by further optimizing the experimental conditions through the response surface method:

[0155] (1) The copper ion content in the electroplating solution was determined to be 113.10 mg / L using an atomic absorption spectrophotometer, and no nickel, iron, or zinc ions were detected. The method of thiourea masking and adding activated carbon was used, but the effect was not good, so the copper extractant ZJ988 was selected for removal. When the pH of the electroplating solution was 3.5 and the ratio of water phase to oil phase was 1:2, 30% of the ZJ988 extractant was used for extraction, the extraction time was 5 minutes, and the water phase was taken for determination after standing for 10 minutes. The measurement results showed that the average extraction rate of copper ions can reach 96.91%, and high-purity copper can be effectively extracted, eliminating the interference of Cu2+ on glucose determination.

[0156] (2) Through single factor experiment and response surface method experimental analysis, the optimal experimental conditions for determining the glucose content in the electroplating solution were obtained as follows: 0.84 mL of phenol, 6.71 mL of sulfuric acid, and 15.50 min of color development time. The predicted glucose content in the sample was 3.1028 mg / mL. Taking into account the actual operation, the actual method parameters were adjusted to 0.80 mL of phenol, 7.00 mL of sulfuric acid, and 15.00 min of color development time.

[0157] (3) Under the best optimized conditions, the glucose content in the three groups of plating solutions was determined. The results showed that the average glucose content in the plating solution was 3.0771 mg / mL, close to the theoretical value of 3.1028 mg / mL, and the RSD was 0.02%, which was less than 1.5%, indicating that the method was feasible and had good accuracy.

[0158] (4) The glucose standard curve constructed by this method has a good linear relationship in the range of 5.0-30.0 μg / mL. The spike recovery experimental result is 100.12%, and the RSD is 0.76%. The RSDs of the instrument precision and repeatability experiments are 0.01% and 0.04%, respectively. This indicates that the instrument precision is high and the method accuracy is good. It can be used to determine the glucose content in lithium battery copper foil electroplating solution.

Claims

1. A method for determining glucose in a lithium battery copper foil electroplating solution, characterized in that: The following steps are involved: A. Sample pretreatment (1) Adjust the pH value of the solution Place 20 mL of the plating solution in a 50 mL beaker, use 0.1 mol / L sodium hydroxide solution and 0.1 mol / L sulfuric acid solution as regulators, monitor the pH value of the solution with a pH meter, and stir while adjusting to make the solution evenly mixed until the pH reaches 3.5; (2) Extraction of copper ions from electroplating solution Measure 5 mL of the adjusted solution in step (1) into a separatory funnel, add 10 mL of 30% ZJ988 extractant at a ratio of water phase to oil phase of 1:2, shake for 5 min, let stand for 10 min, and take the water phase for later use; (3) Preparation of sample solution Measure 0.5 mL of the extract after extraction in step (2) into a 100 mL volumetric flask, add deionized water to dilute to the scale, mix well and set aside; B. Determination of copper, nickel, iron and zinc Turn on the power of the mainframe and hollow cathode lamp detector of the atomic absorption spectrophotometer and preheat for 15 minutes. At the same time, set the element detection parameters, turn on the air acetylene, air compressor and vacuum box switches in turn, ignite after everything is ready, and follow the prompts to draw the standard solution calibration curve and measure the metal ion absorbance in the electroplating solution, and then calculate the metal ion content in the electroplating solution according to the linear regression equation of the standard solution. Parallel determination is performed 3 times; C. Determination of glucose The sample solution is developed by the phenol-sulfuric acid method, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 mL of glucose standard solution are measured and placed in 25 mL stoppered colorimetric tubes, respectively, and water is added to 2.0 mL, and 2.0 mL of the sample solution in step (3) is taken, and distilled water is used as a reference; 0.8 mL of 6% phenol solution is added and shaken, and 7 mL of concentrated sulfuric acid solution is immediately added, and the mixture is placed at room temperature for 5 minutes, and then the mixture is colorized in a hot water bath at a temperature of 50° C. for 15 minutes, and then the mixture is cooled to room temperature in a cold water bath for 45 minutes; the absorbance is measured in a UV-visible spectrophotometer at a wavelength of 490 nm, and a regression equation is drawn to calculate the glucose content in the sample; D. Calculation formula The metal ion content is calculated according to formula (1): Where: X——the content of the substance to be tested in mg / mL; Cx——mass concentration of any metal ion in the sample, mg / mL; D——sample dilution multiple; m——sample transfer volume, mL; The extraction rate is calculated according to formula (2): Where: R——extraction rate, %; C0, Ce——Concentration of the ion to be measured in the solution before and after extraction, mg / L; Glucose content is calculated according to formula (3): Where: m——sample transfer volume, mL; 1000——conversion factor; CA——glucose mass concentration in the sample, μg / mL; V——sample volume, mL; The spike recovery rate was calculated according to formula (4): Where: P——spike recovery, %; C1——concentration of sample before spike addition, mg / mL; C2——concentration of sample after spike, mg / mL; C3——Concentration of standard solution added, mg / mL.